Kaposi's Sarcoma-Associated Herpesvirus (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
The discovery of KSHV in 1994 was a historical landmark in tumor virology and human cancer research. Its subsequent identification as a cause of Kaposi sarcoma and in association with primary effusion lymphoma and multicentric Castleman disease soon attracted up to hundreds of research laboratories and thousands of virologists and oncologists to switch their research directions. To date, PubMed has collected nearly 5000 papers on KSHV from numerous journal publications in the world. These studies reiterate that the global fight against human cancers will continue to receive great support from our tremendous efforts in searching for new tumor-causing viruses and in understanding the basic biology of tumor viruses. To celebrate the 20th years of KSHV discovery, I am very proud to be an invited Guest Editor for a special issue on KSHV in the journal "Viruses" and happy to assemble all published articles from the special issue into this book, Kaposi Sarcoma Associated Herpesvirus. The collected articles cover almost all aspects of KSHV, including updated reviews and research articles on KSHV epidemiology and transmission, KSHV interaction with host cell receptors and cell entry, KSHV latency and latency-associated nuclear antigen (LANA), molecular biology of KSHV lytic reactivation and lytic switch control by KSHV ORF50 and other factors, KSHV post-transcriptional regulator ORF57, molecular biology of KSHV polyadenylated nuclear RNA (PAN RNA) and PAN as a lncRNA in epigenetic gene regulation of KSHV, viral mimics of cellular genes in KSHV infection and disease, KSHV targeted therapy, KSHV miRNAs and vGPCR, etc. In particular, I am greatly honored to have Yuan Chang and Patrick Moore to mark the first 20 years of KSHV research by recounting the historical stories leading to their astonish discovery and Science publication of KSHV that has led us where we are today. The book is also intended to assist Medical students and residents, dermatologists, hematologist, oncologists, and other related specialties to understand what we have known about KSHV and its infections and pathogenesis.